Flipped classroom teaching as a tool to enhance self-directed learning among first MBBS students - Jawalekar, Seema; Gupta, Garima; Kumawat, Priyanka (International Journal of Research in Medical Sciences, 2024)
Background: Medical education shifts from a teacher-centered to a student-centered which fosters self-directed learning, critical thinking, and problem-solving skills, especially in the scenario of a large classroom. Flipped classroom is a blended learning to increases student engagement with content, improves faculty contact time with students, and enhances learning. This study was conducted to compare the effectiveness of the flipped classroom method and didactic lecture on students’ performance and to obtain students’ and teachers’ perceptions in teaching-learning biochemistry. Methods: All participant students were randomly divided into two groups and subjected to the FC method and TDC method in module A and a crossover of groups was done in module B. Both groups were subjected to pre and post-tests after intervention in modules. Feedback was obtained from students and teachers on both learning methods. Results: There was a statistically significant difference (P < 0.0001) after applying independent t-test in pre and post-test scores and module completion test in both learning methods. About 91% of participants were satisfied with using a flipped classroom and found it more enjoyable, creates interest in the subject, whereas faculties’ feedback shows it requires more efforts and time. Conclusions: Considering responses and results of the assessment, it can be concluded that the FC approach, effectively engage students in the learning process, inculcation the attributes to develop self-directed and lifelong learning skills. Also improved the students’ performance and perceptions of the learning experience. Most of the students indicate that this approach is worth to use in future.